Learning of a simple grapho-motor task by young children and adults: similar acquisition but age-dependent retention - Julius, Mona S.; Adi-Japha, Esther (Frontiers in Psychology, 2015)
Many new skills are acquired during early childhood. Typical laboratory skill learning tasks are not applicable for developmental studies that involve children younger than 8 years of age. It is not clear whether young children and adults share a basic underlying skill learning mechanism. In the present study, the learning and retention of a simple grapho-motor pattern were studied in three age groups: 5-6 years, 7-8 years, and 19-29 years. Each block of the task consists of identical patterns arranged in a spaced writing array. Progression across the block involves on-page movements while producing the pattern, and off-page movements between patterns. The participants practiced the production of the pattern using a digitizing tablet and were tested at 24 hours and two weeks post-practice. All age groups produced the task blocks more quickly with practice, and the learning rate was inversely related to the initial production time across and within the groups. All groups exhibited additional gains 24 hours post-practice that were well retained 2 weeks later. The accuracy of the participants was maintained throughout the two-week period. These findings suggest that young children and young adults use a similar mechanism when learning the task. A separate analysis of the on-page and off-page movement times per block indicated that during retention testing, the 6-year-olds spent more time off-page than when tested at 24 hours post-practice, thus supporting the notion that an age advantage may exists in the long-term retention of skills due to planning-dependent aspects.